A Review of Flexural Strength on Self-healing Concrete Using Bacillus as Self-healing Agent - Mohd Hanafiah, Hazirah Izni; Mokhtar, Norfaniza (Recent Trends in Civil Engineering and Built Environment, 2023)
Concrete is the most widely utilized construction material in the world. Hence, construction industry development required to improve on material to ensure the concrete high functionality. Cracks in concrete are very common either macro or micro cracks. The cracks will affect the durability of concrete especially on important structure such as beam. Objective of this study is to study the effect on the flexural strength of self-healing concrete and study the performance of bacteria on self-healing concrete with different bacteria concentration. Introduction bacteria into concrete received a lot of interest. Bacteria will aid in mineral precipitation of pores and tiny cavity areas. Bacillus is a type of bacteria that can produce calcium carbonate (CaCo3) to enhance the concrete characteristic. Bacillus family bacteria and flexural strength of concrete is the limitation of this study. Method of this study is using systematic review. The review used to evaluate the objective of this study. Boolean operators play important role in searching the database.  In this study, the effect of bacteria concentration on self-healing concrete shows an increment on the flexural strength of concrete at certain range of concentration which is from 101 until 105 cell/ml. Result in this study shows that 105 bacterial is the optimum concentration that flexural strength of the concrete at the highest.